Response of Yield and Quality Attributes to Plant Spacing In potato Growing. - Ekyatuheire, Maryusita (Kabale University, 2025)
Potato (Solanum tuberosum) is a staple food crop worldwide, contributing significantly to food security and economic stability in many regions. One factor that significantly influences potato productivity and quality is plant spacing which is the distance between individual plants within a crop plantation. Optimizing plant spacing can potentially enhance photosynthetic efficiency, improve nutrient uptake, and reduce competition among plants, thereby impacting yield and quality attributes. The study aimed at evaluating the effect of spacing on potato yields and quality attributes. The study used a randomized complete block design with replications and data was collected on plant height, leaf area index, yields, and quality. It was found that spacing has a significant effect on plant height and leaf area index but an insignificant effect on yields and quality which implied that there are other factors that affect quality and yield beyond spacing. Therefore, it was recommended that farmers practice spacing since plant height was associated with high yields but there was a need for participatory sharing of experiences by experts, traditional farmers, and extension workers to make informed decisions on the optimal spacing.